Self-efficacy, gaming motives, social support and internet gaming disorder among emerging adults in Malaysia - Chang, Ke Jing; Ang, Colette Chien Yueh; Goh, Hui Shan (2024)
Nowadays, Internet games served as a leisure online activity for the public, but people still heavily utilise them, leading to addictive behaviours. This research aimed to investigate the predictive roles of self-efficacy, gaming motives (social motive, escape motive, competition motive, coping motive, skill development motive, fantasy motive, recreation motive), social support, and Internet gaming disorder (IGD) among emerging adults in Malaysia. Social Cognitive Theory (SCT) was used and suggested that addiction behaviour was influenced by the expectations regarding the reinforcement or consequences associated with a particular behaviour. A purposive sampling method was used to collect 354 Malaysian participants between 18 and 29 years old, with a minimum of 12 months of gaming experience. Internet Gaming Disorder Scale 9-Short-Form, New General Self-Efficacy Scale, Motives for Online Gaming Questionnaire, and Brief Form of the Perceived Social Support Questionnaire were utilised to measure the variables. The results showed that self-efficacy was a significant positive predictor of IGD, while escape motive, and competition motive were significant negative predictors of IGD. Social motive, coping motive, skill development motive, fantasy motive, recreation motive, and social support showed non-significant predicted IGD. In conclusion, the findings from this study have provided a better understanding of the predictive factor of IGD among emerging adults in the Malaysia context which was valuable in identifying gaps in the literature regarding the pathological issues of gaming in the education sector, early intervention, prevention, and treatment of IGD in Malaysia.